Agreement between Arterial and Capillary pH, pCO2, and Lactate in Patients in the Emergency Department - Vincent Collot; Stefano Malinverni; Jabir Haltout; Eric Schweitzer; Pierre Mols; Magali Bartiaux (Emergency Medicine International)
Background. Blood gas analysis (BGA) is a frequent painful procedure in emergency departments. The primary objective of the study was a quantitative analysis to assess the mean difference and 95% confidence interval of the difference between capillary and arterial BGA for pH, pCO2, and lactate. Secondary objective was to measure the sensitivity and specificity of capillary samples to detect altered pH, hypercarbia, and lactic acidosis. Adults admitted to the ED were screened for inclusion. We studied the agreement between the two methods for pH, pCO2, and lactate with Bland-Altman bias plot analysis and receiver operating characteristic curves. Results. One hundred ninety-seven paired analyses were included. Mean difference for pH between arterial and capillary BGA was 0.0095, and 95% limits of agreement (LOA) were −0.048 to 0.067. For pCO2, mean difference was −0.3 mmHg, and 95% LOA were −8.5 to 7.9 mmHg. Lactate mean difference was −0.93 mmol/L, and 95% LOA were −2.7 to 0.8 mmol/L. At a threshold of 7.34, capillary pH had 98% sensitivity and 97% specificity to detect acidemia; at 45.9 mmHg, capillary pCO2 had 89% sensitivity and 96% specificity to detect hypercarbia. At a threshold of 3.5 mmol/L, capillary lactate had 66% sensitivity to detect lactic acidosis. Conclusion. Capillary BGA cannot replace arterial BGA despite high concordance between the two methods for pH and pCO2 and moderate concordance for lactate. Capillary measures had good accuracy when used as a screening tool to detect altered pH and hypercarbia but insufficient sensitivity and specificity when screening for lactic acidosis.